PERTUMBUHAN DAN PERKEMBANGAN ORGANISASI-ORGANISASI ISLAM: MUHAMMADIYAH, NAHDATUL ULAMA DAN JAMI’ATUL WASHLIYAH - M Fadli (Pascasarjana UIN Sumatera Utara, 2021)
Awareness of organization with a very high effort and imbued with feelings of nationalism and religion led to developments and a new era in education and teaching. With full awareness, the leaders of the movement tried to change the backwardness of the Indonesian people through the implementation of national education. Their efforts are realized by establishing schools and madrasas with a modern system by adopting a Western education system that teaches general subjects and religious subjects. Evidence of this development is until the birth of Islamic universities in Indonesia. The role of these organizations can be extraordinary, both in the fields of economy, education, politics and in achieving independence for the Indonesian state. We also feel this until now where many Islamic organizations still exist and maintain stability in Indonesia within a government.